Eighteen cases of wheat allergy and wheat‐dependent exercise‐induced urticaria/anaphylaxis sensitized by hydrolyzed wheat protein in soap. (20th June 2015) - Kobayashi, Tomoko; Ito, Tomonobu; Kawakami, Hiroshi; Fuzishiro, Kanzan; Hirano, Hirofumi; Okubo, Yukari; Tsuboi, Ryoji
Abstract Background Glupearl 19S, an acid‐hydrolyzed wheat protein (HWP), is used widely in Japan as a moisturizing ingredient in facial soaps. Since 2010, there has been an increasing number of reports of contact urticaria and wheat allergy resulting from the use of products containing this substance. Case reports Sixty‐one patients who had used HWP‐containing facial soap visited our hospital. Thirty‐five of these experienced urticaria or anaphylaxis after consuming wheat‐containing food. Results Eighteen of the 35 patients tested positive to 0.01% Glupearl 19S solution. Wheat‐specific IgE and serum gluten‐specific IgE were higher in the patients with HWP allergy than in non‐HWP allergy patients. Among the patients who tested positive to Glupearl 19S on the skin prick test, nine experienced HWP–wheat‐dependent exercise‐induced anaphylaxis, and four experienced food‐dependent anaphylaxis. Moreover, four of these patients not only experienced food‐dependent anaphylaxis but also a worsening of the symptoms during exercise. Discussion The clinical symptomology was so variable that the patients were classified into six groups. We found that patients with HWP allergy tended to manifest symptoms of both HWP–wheat‐dependent exercise‐induced anaphylaxis and contact urticaria. The etiology of hydrolyzed wheat protein allergy is unknown. Patients with a history of these symptoms need to be informed about the risk of consuming wheat‐containing foods and the importance of excluding such items from their diet.